Ultrasound evaluation of small intestinal thickness and a comparison to body weight in normal chickens (Gallus gallus domesticus). Issue 1 (28th January 2019) - Garrett, K; Milne, M; Doneley, R; Perkins, N
Abstract : Background: Ultrasound in avian patients is useful for identifying abnormalities within the coelomic cavity. A correlation between sonographic evaluation of jejunal thickness and body weight has been reported in mammals, but not the chicken ( Gallus gallus domesticus ). The purpose of this study was to prospectively assess the normal values of jejunal thickness in the chicken and compare this to body weight. Methods: Coelomic ultrasound was performed on 89 clinically normal chickens with no history or signs of gastrointestinal disease. Two populations of hens (commercial layers and backyard purebred and mixed‐breed hens) were used. Breed and ultrasonographically measured jejunal wall thickness were recorded in all hens. Body weight was recorded in 45 of the hens (mixed‐breed and purebred backyard chickens). Results and conclusion: There was no statistically significant correlation between body weight and ultrasonographically measured jejunal wall thickness. The mean thickness of the jejunal wall in healthy chickens was 2.1 ± 0.08 mm. Further studies comparing jejunal thickness in chickens with and without signs of GI disease would be useful.